Asuhan Kebidanan Komunitas pada Keluarga Tn. P dengan Anemia Ringan pada Ibu Hamil di Dusun Aik Lengis Desa Kuta Kecamatan Pujut - Tika Fitriani; Hulfa Ahadian Haryanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The purpose of this study is to improve the health status of families so that healthy and prosperous families are realized. The study was conducted by collecting all available data through interview techniques and physical and supporting examinations. Subjective data, especially on the main complaint, namely the mother said she was weak, dizzy, tired quickly, short of breath and pain in the waist and legs. And objective data, namely the mother's general condition was good, anemic conjunctiva and Hb levels of 9.2 g%. The results of the study are the need for immediate action and collaboration on Mrs. A with mild anemia in Aik Lengis Hamlet, Kuta Village with the result that in this case no collaborative action was taken because there were no indications and data to support the action. Has determined a midwifery care action plan for Mrs. A with mild anemia in Aik Lengis Hamlet, Kuta Village with the results of planning care based on actual diagnoses/problems and potential problems that can occur and evaluating the results of the actions that have been carried out on Mrs. A with mild anemia in Aik Lengis Hamlet, Kuta Village with the result that the care that has been given was successful as indicated by changes in the mother's Hb levels which were initially 9.2 g% to 10.8 g%.